f(x)=4x+3
helpp

- anonymous

f(x)=4x+3
helpp

- Stacey Warren - Expert brainly.com

Hey! We 've verified this expert answer for you, click below to unlock the details :)

- katieb

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

- whovianchick

What are we helping to do?

- anonymous

figure out f(x)=4x+3

- anonymous

can you walk me through it

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

- whovianchick

What do you mean figure it out? What are the instructions on the problem?

- anonymous

how do you do it

- anonymous

f(x) = 4x + 3 is a statement, not a question. What are you trying to do with the function?

- anonymous

get like an answer at the end what would i tell my teacher

- anonymous

what were you asked? there has to be some instructions

- anonymous

evaluate it

- Vocaloid

did they give you any other information?

- Vocaloid

like, did they give you an x value?

- anonymous

ok, now we're getting somewhere. Are you supposed to evaluate it at a specific value of x?

- anonymous

lets say x is 2

- anonymous

ok, so you would substitute 2 for x
f(x) = 4x + 3
f(2) = 4(2) + 3
then simplify that

- whovianchick

Don't multiply f and 2 though, that's basically y. It stays f(2), or function of 2.

- anonymous

ok

- anonymous

11

- anonymous

yep

- anonymous

can i ask a couple more

- anonymous

ok

- anonymous

f(x)=2x+4
G(x)=X+1

- anonymous

no actually

- anonymous

f(x)=5x+3
G(x)=x+4

- anonymous

ok what are the instructions for this one?

- anonymous

i have to combine them but I'm confused

- anonymous

ok, there are lots of different ways to combine functions. It really depends on what you're asked for. Do you have a specific combination, or do you just want me to show you some

- anonymous

can you show me some

- anonymous

ok let's start with the basic 4
Adding
\(f(x) + g(x) = 5x + 3 + x + 4\)
\(= 6x + 7\)
Subtracting
\(f(x) - g(x) = 5x + 3 - (x + 4)\)
\(=5x+3-x-4\)
\(=4x-1\)
\(g(x) - f(x) = x + 4-(5x+3)\)
\(=x+4-5x-3\)
=\(-4x+1\)
Multiplying
\(f(x)\cdot g(x)=(5x+3)(x+4)\)
\(=5x^2+20x+3x+12\)
\(=5x^2+23x+12\)
Dividing
\[\frac{ f(x) }{ g(x) }=\frac{ 5x+3 }{ x+4 }\]
\[\frac{ g(x) }{ f(x) }=\frac{ x+4 }{ 5x+3 }\]

- anonymous

Then you can get more complex with something like
\(2f(x)-3g(x)=2(5x+3)-3(x+4)\)
=\(10x+6-3x-12\)
=\(7x-6\)

- anonymous

You can also compose functions, which is basically putting one inside the other.
To find f(g(x)) replace the x in f(x) with the function from g(x).
\(f(g(x))=5(x+4)+3\)
\(=5x+20+3\)
\(=5x+23\)
To find g(f(x)), do the opposite and replace the x in g(x) with f(x)
\(g(f(x))=(5x+3)+4\)
\(=5x+7\)

- anonymous

ok can you walk me through on
Subtracting
f(x)−g(x)=5x+3−(x+4)
=5x+3−x−4
=4x−1
g(x)−f(x)=x+4−(5x+3)
=x+4−5x−3
=−4x+1
how'd you get that

- anonymous

from the first line to the second you have to distribute.
-(x + 4) = -x - 4 for the first one
and -(5x + 3) = -5x - 3
then you combine like terms
Is that what you meant?

- anonymous

yea thank you and what about the others sorry I'm asking so much its just that i need to pass this

- anonymous

no problem. for multiplying you usually have to use FOIL or do some distribution.
dividing is just writing one on top of the other like a fraction

- anonymous

ok

- anonymous

Most of this is really knowing how to apply the distributive property and combine like terms

- anonymous

ok thank you

- anonymous

you're welcome

Looking for something else?

Not the answer you are looking for? Search for more explanations.